"The assessment of odontophobia among Syrian refugees at the Moroccan military medical and surgical hospital in the Zaatari camp in Jordan and its influence by post-traumatic stress disorder : about an epidemiological investigation". - Mehdi, Hariri El; Mohamed, Sellouti; Jaouad, Nguadi; Hakima, Chhoul (Jour Med Resh and Health Sci, 2020)
Introduction : Odontophobia is a complex anxiety disorder related to excessive fear of dental care. Of multifactorial origin, it affects more females than males at all ages. Odontophobia can also be associated with other disorders, namely post-traumatic stress disorder (PTSD), which is recognized in refugees from civil wars. Materials and methods : Descriptive and analytical cross-sectional epidemiological study, carried out during February 2020 at the Syrian refugee camp in Zaatari, Jordan, involving 200 consultants at the dental office to assess their degree of odontophobia and to determine the risk factors associated with this disorder, particularly post-traumatic stress disorder (PTSD). Results : The authors collated 200 subjects of which 125 (62.5%) were phobic with a corah score (> or = to 13) and 75 (37.5%) were non-phobic with a corah score (< to 13). The sex ratio was statistically different between the two populations with a predominance of female sex (p=0.025). odontophobia is also related to the length of time spent in Syria during the civil war, it is observed more in 96 (48%) patients who spent between (13 and 24 months) (p=0.017). Similarly, odontophobia is influenced by post-traumatic stress disorder in its severe form (p=0.011). Conclusion: Descriptive and analytical observational epidemiological study showing the high prevalence of odontophobia among Syrian refugees consulting at the dental office of the Moroccan military medical-surgical hospital in Zaatari camp in Jordan and its influence by post-traumatic stress disorder (PTSD).